Conformism, Non-Conformism and Anti-Conformism in the Culture of the United States - T. Tsimpouki; Antonis Balasopoulos; Gesa Mackenthun (Heidelberg: Universitätsverlag Winter, 2008)
The essays collected in this volume – the outcome of the EAAS convention in Cyprus in 2006 – form a crossroads between a number of disciplines (literary theory and criticism, film studies, history, cultural studies, sociology); they are all animated – in different ways and to different extents – by a healthy suspicion towards the idea that the concepts of conformism, non-conformism and anti-conformism are transhistorically static or transcendentally self-evident. The conceptual contours of the subject are investigated before the topic is then explored in historical perspective, in its textual manifestations, and with regard to its stakes in visual culture. The collection is rounded off with a critical glance at commercial aspects of conformism and anti-conformism. The volume includes essays by Donald Pease, Heinz Ickstadt, Susana Delfino, Albena Bakratcheva, Marek Wilczynski, Johannes Völz, Marc Amfreville, Andrew S. Gross, Yves-Charles Grandjeat, Thomas Pughe, Susanne Rohr, Peter Loizos, Dimitris Liokaftos, Hilaria Loyo, Alexandra Ganser and Karin Hoepker, Frank Mehring, Berndt Ostendorf, and Arthur Redding.